Grau de monopólio e testes de Granger: Causalidade entre custos e preços na indústria brasileira (1978-1998) - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2000)
– This paper analyses the role of relationship among suppliers and buyers of inputs in condition of bilateral oligopoly, using the kaleckian concept of monopoly degree. It finds that the tradeoff among sectors alters the degree of monopoly of the sectors, and consequently of the economy as a whole. Then, Granger's causality tests are done among input prices and final product prices for 10 sectors of the manufacturing industry. The main conclusion is that the buyers have more ability to influence the prices than the suppliers.
Keywords: 330; Marktstruktur; Monopol; Kausalanalyse; Industrie; Brasilien